Effects of Neck Strength Training on Isometric Neck Strength in Rugby Union Players - Geary, K.; Green, B. S.; Delahunt, E. (Clinical Journal of Sport Medicine, 2014)
Objective: To investigate the effectiveness of a neck strengthening program on the isometric neck strength profile of male rugby union players.